Implementasi Model Pembelajaran Cooperative Learning Tipe STAD dalam Pembelajaran Insya’ - Aisyatul Hanun; Amirul Mukminin (STUDI ARAB, 2019)
MTs SA Al-Hidayah is on of schools with islamic boarding that apllied the language environment. One class of extracurriculer learning is insha’class. Insha’ is a kind of writing learning in Arabic Skills. This MTs was established in 2011 which was founded by AIBEP through the Indonesian Ministry of Religion. For eight years for eight years the school has grown rapidly. since five years ago the environment of Arabic and English was applied. one of them is the Arabic writing skills class. that is to train students to have writing skills from the basic level, at least to the middle level. This is to motivate students to enthusiastically read Arabic texts so they can hone their writing skills. The author conducted qualitative research because he saw the ability of students in MTs SA Al-Hidayah who could be classified as active Arabic-speaking students, both toeori (language rules) and practice (reading, oral and written communication). Insha teachers in extracurricular activities use several learning methods to improve students' writing motivation and ability. one of them is a cooperative leaning type STAD learning model. in this learning model the teacher is required to be more active in the evaluation of learning, while in the learning process students have more activity than the teacher. The advantages of this method is the enthusiasm of students in learning, and spontaneously they do small discussions before writing or answering questions. so, they will have a lot of learning experience and knowledge sharing with each other.